TEKNIK PEMERIKSAAN KEDOKTERAN NUKLIR PADA KELENJAR TIROID - Raditya Faradina Pratiwi; Eri Puspita Sari (Perhimpunan Radiografer Indonesia (PARI), 2022)
ABSTRACT Background: Thyroid scan is an examination of the thyroid with a gamma camera that aims to obtain functional morphological images of the thyroid and assess the ability of the thyroid gland to capture radioactive substances. From some literature that researchers reviewed, there were differences in thyroid scan procedures, such as the use of radiopharmaceuticals, the time interval for imaging after radiopharmaceutical administration (static image), and projections to produce images of the thyroid gland.. Methods: This type of research is a library research or literature review by reviewing as many as 50 journals related to Nuclear Medicine Examination during the last 10 years. Then the researchers screened the journals related to the thyroid scan examination of the thyroid gland in as many as 4 journals Results: Based on the review results, to diagnose hyperthyroidism, use 99mTc with a static image time of 15-20 minutes & 123I with a static image time of 24 hours. Use of 99mTc & 131I to detect intrathoracic goiter causing hyperthyroidism, with a static image time of 20 min after 99mTc04, and 24 hours after 131I; The projections used were anterior & posterior thoracic and anterior neck with markers on the inferior isthmus for the 99mTc 04 scan, whereas those for 131I scans were only anterior projections. And to diagnose ectopic thyroid, using AP, RAO, & lateral projection after 10 min of 99mTc 04 injection, as well as post water anterior projection, lateral view is useful for localizing other tracer uptake. Conclusions : Several techniques and uses of radiopharmaceuticals in thyroid scan examination are based on the clinical findings and the objective of the evaluation of the thyroid gland itself. The use of the right technique can greatly help the radiologist to diagnose abnormalities in patients.